Air Temperature and Humidity Monitoring System for Server Rooms and Data Centers Using the Fuzzy Tsukamoto Method with IoT - JB, Salwa Nur; Huzaeni, Huzaeni; Salahuddin, Salahuddin (Journal of Artificial Intelligence and Software Engineering, 2024)
Lhokseumawe State Polytechnic has UPT Information and Communication Technology (ICT) Data Center that manages important infrastructure for the teaching and learning process. This study aims to design and build an IoT-based air temperature and humidity monitoring system, using Fuzzy Tsukamoto algorithms to handle highly variable sensor data. Blackbox testing showed that the system managed to provide real-time server room condition information and send notifications when conditions reached a certain limit. Turning the AC on and off and incandescent lamps also work well. Whitebox testing successfully ensures that Tsukamoto's Fuzzy algorithm is implemented correctly and that hardware integration runs without problems. The Blackbox test managed to achieve 100% da success on and the Whitebox only achieved 100% on both Tests.